2011
DOI: 10.1155/2011/146865
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Cystatin-C-Based Estimated Glomerular Filtration Rates in Healthy Young Adults: Results of a Clinical Trial

Abstract: Recently it has been reported that the estimated glomerular filtration rate (eGFR) is higher in habitual coffee consumers than in noncoffee consumers. However, the causality remains unclear. Therefore, we conducted a clinical trial to investigate the effects of coffee consumption on kidney function. Nineteen asymptomatic nonsmokers aged 21–27 years old participated in this study. They consumed coffee (18 g coffee beans/450 mL per day) or green tea as a comparator for 2 weeks in a crossover design. Although cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…Coffee consumption led to increased concentrations of adiponectin in several intervention studies (4)(5)(6). Similarly, coffee consumption was related to higher adiponectin concentrations among women in our study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Coffee consumption led to increased concentrations of adiponectin in several intervention studies (4)(5)(6). Similarly, coffee consumption was related to higher adiponectin concentrations among women in our study.…”
Section: Discussionsupporting
confidence: 80%
“…During recent years, a number of epidemiologic studies have found an inverse relationship between consumption of coffee and the risk of developing type 2 diabetes (T2D) 4 (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of coffee and tea consumption on renal function, however, has been poorly investigated. In a cohort of Japanese adults, the consumption of coffee, but not tea, was associated to increased eGFR [140]. The same findings have been reported in another two studies performed in Japan [141,142].…”
Section: Green Tea and Coffeesupporting
confidence: 85%
“…The results were significant and independent of the added sugar and level of high sensitivity C-reactive protein. One clinical trial of 19 young adults aged 21 to 27 years also showed that the consumption of ≥ 3 cups of coffee per day for 14 consecutive days is significantly associated with increased cystatin C-based eGFR as compared with subjects who consume green tea consumption 9). This finding suggests that even a short period of coffee consumption may have a favorable effect on kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Among such studies, an inverse association between coffee consumption and diabetes has been identified by a systematic review 6). Although there is a paucity of knowledge regarding the relationships between coffee consumption and the risk of renal function impairment, recent small-sized Japanese studies have suggested that habitual coffee consumption may be associated with normal or increased estimated glomerular filtration rate (eGFR) 7-9). Since renal function impairment is often caused by diabetes, even in the early stage of pathogenesis,10) one could speculate that coffee consumption may have favorable effects on kidney function via antidiabetic effects.…”
Section: Introductionmentioning
confidence: 99%